Pengaruh Pembelajaran Realistic Mathematic Education Terhadap Kemampuan Literasi dan Disposisi Matematis di SMP Negeri 4 Randudongkal - Muhammad Masyhuri Irham (AlphaMath : Journal of Mathematics Education, 2020)
This research was aimed at defining the effect of Realistic Mathematic Education (RME) on students’ mathematical literacy ability and disposition. This research applied the Posttest-Only Control Design. The population was all grade VII students of SMP Negeri 4 Randudongkal. The Cluster Random Sampling was used in this research and it gained class VII B as the experiment group and class VII E as the controlled group. The data on students’ Mathematical literacy ability were collected through the post-test, while the data of students’ mathematical disposition were collected through questionnaires. The research hypothesis was comparative with the right-side test. The data were analyzed using the Mann Whitney test. With the significant value of 5%, it was revealed that students’ Mathematical literacy ability and disposition attending the learning process using RME were better than those who were not. It could be concluded that the RME learning method had a significant and positive effect on the students' mathematical literacy ability and disposition.